Gender & censorship - Bose, Brinda (Issues in contemporary Indian feminism, 2006)
section 1. Laws, structures, guidelines -- section 2. The representation of women in the media and the women's movement -- section 3. The indecent representation of women act and further debates -- section 4. New directions on censorship in feminist theory/praxis
Includes bibliographical references; Serienzählung nur auf Schutzumschlag
Keywords: Aufsatzsammlung; Zensur; Frau; Massenmedien; Indien